18F-PSMA-1007 Uptake in Pulmonary Lymphangitic Carcinomatosis Metastasis From Prostate Cancer. (July 2021) - Liu, Bo-Le; Hong, Jun-Jie; Tang, Kun; Lin, Jie; Zheng, Xiang-Wu
Abstract : Abstract: A 55-year-old man with cough, bone pain, and cervical lymphadenopathy underwent both 18 F-FDG and 18 F-PSMA-1007 PET/CT scans with clinical suspicion of malignant disease. Compared with 18 F-FDG PET/CT, 18 F-PSMA PET/CT showed intense tracer uptake in the prostate gland, lungs, osteogenic lesions, and multiple lymph nodes. Interestingly, we also found the high tracer concentration of pulmonary lymphangitic carcinomatosis, a very rare form of prostate cancer metastasis to the lung, on 18 F-PSMA-1007 PET/CT images.